Nonlinear analysis of lightweight aggregate concrete columns - Kołodziejczyk, Ewelina; Waśniewski, Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The paper presents a numerical analysis of deformability and load-bearing capacity of lightweight aggregate concrete (LWAC) elements subjected to bending with axial force. The nonlinear material model of LWAC presented in Eurocode 2 (EC2) was assumed. Several different densities and compressive strengths of concrete were taken into account. The investigations included the comparison of the sectional capacity and the behaviour of slender elements made with normal and lightweight aggregate concrete. It was observed that density-dependent mechanical properties of concrete affect the obtained values of the maximum axial force and the bending moment despite the same mean compressive strength. In every case, the capacity of the RLWAC section was lower than the one of normal weight, which was caused by a linear characteristic of the LWAC. Other important factors were the modulus of elasticity and the ultimate strain of concrete. LWAC with the higher density and the lower ultimate strain gave greater stiffness to slender columns but reduced the cross-sectional capacity. It was concluded that the elastic modulus and the peak strain of LWAC which are applied in columns calculations should be verified experimentally.